2016
DOI: 10.1038/srep34747
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 promotes brown adipocyte phenotype

Abstract: Nesfatin-1, an 82 amino acid gastric peptide, is involved in regulation of food uptake and in multiple metabolic activities. Whether nesfatin-1 modulates the differentiation and lipid metabolism of brown adipocytes remains unknown. In the present study, we found that nesfatin-1 mRNA and protein were detectable in isolated brown adipocytes and gradually decreased during differentiation (95% CI 0.6057 to 1.034, p = 0.0001). The decrease in nesfatin-1 was associated with a significant reduction in p-S6. Exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Compatible with these findings, nesfatin-1 treatment promotes Atgl as well as Ucp1 and Pgc1a mRNA expression in brown adipocytes in vitro (Wang et al 2016), thus implying that nesfatin-1 can also act peripherally to control lipid utilization and iBAT thermogenesis. Interestingly, it was also reported in the same study that nesfatin-1 is produced by brown adipocytes, suggesting autocrine regulation (Wang et al 2016). However, to what extent locally produced or circulating nesfatin-1 contributes to iBAT thermogenesis remains to be investigated.…”
Section: :2supporting
confidence: 58%
See 1 more Smart Citation
“…Compatible with these findings, nesfatin-1 treatment promotes Atgl as well as Ucp1 and Pgc1a mRNA expression in brown adipocytes in vitro (Wang et al 2016), thus implying that nesfatin-1 can also act peripherally to control lipid utilization and iBAT thermogenesis. Interestingly, it was also reported in the same study that nesfatin-1 is produced by brown adipocytes, suggesting autocrine regulation (Wang et al 2016). However, to what extent locally produced or circulating nesfatin-1 contributes to iBAT thermogenesis remains to be investigated.…”
Section: :2supporting
confidence: 58%
“…However, the latter can be induced by peripheral nesfatin-1 administration, as it was inferred from a decrease in the respiratory quotient in indirect calorimetry (Mortazavi et al 2015). Compatible with these findings, nesfatin-1 treatment promotes Atgl as well as Ucp1 and Pgc1a mRNA expression in brown adipocytes in vitro (Wang et al 2016), thus implying that nesfatin-1 can also act peripherally to control lipid utilization and iBAT thermogenesis. Interestingly, it was also reported in the same study that nesfatin-1 is produced by brown adipocytes, suggesting autocrine regulation (Wang et al 2016).…”
Section: :2mentioning
confidence: 74%
“…Consistently, increase of nesfatin‐1 has been detected in TG mice in which mTOR signaling is activated specifically in X/A‐like cells (data not shown). In addition, we have demonstrated that nesfatin‐1 promotes the differentiation of brown adipocytes . However, until the receptor for nesfatin‐1 is characterized, it is not possible to efficiently block the action of nesfatin‐1, and therefore to confirm that increase of nesfatin‐1 in TG mice contributes to metabolic effects in TG mice.…”
Section: Discussionmentioning
confidence: 96%
“…Activation of mTOR induced by leucine or deletion of TSC1 decreased expression of the brown adipocyterelated genes UCP1, UCP3, PGC-1α and PRDM16, as well as COX8B and ATP5B. Both leucine and TSC1 deletion blocked nesfatin-1-induced up-regulation of UCP1, PGC-1α, COX8B and ATP5B expression in differentiated brown adipocytes (Wang et al, 2016). The results of the present study showed a significant and positive correlation between PGC-1α gene expression and serum levels of nesfatin-1, which is probably because of mTOR activator elements, as mentioned above.…”
Section: Discussionmentioning
confidence: 96%
“…Intracerebroventricular injection of nesfatin-1 inhibits food intake in a dose-dependent manner, resulting in a decrease in total body fat and body mass loss, while anti-nesfatin-1 increases the intake of food in male rats (Oh et al, 2006). It was reported that nesfatin-1 promotes the differentiation of brown adipocytes through PGC-1α (Wang et al, 2016). Hypothalamic resistin seems to be a key regulator of the brain-fat axis which regulates energy homeostasis (Rodríguez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%